Embellishments for adventurous sewing : master appliqué, decorative stitching, and machine embroidery through easy step-by-step instruction and fun projects /: master appliqué, decorative stitching, and machine embroidery through easy step-by-step instruction and fun projects. (2013) - Unknown
No abstract available